Paravertebral abscess formation due to brucellosis in a patient with ankylosing spondylitis - Ozgocmen, S; Ardicoglu, A; Kocakoc, E; Kiris, A; Ardicoglu, O (Editions Scientifiques Medicales Elsevier, 2001)
It is occasionally difficult to distinguish the features of spinal brucellosis from those of ankylosing spondylitis (AS), and the resultant delayed diagnosis may allow insidious progression of the complications of the brucella infection, The case of a 33-year-old male HLA-B27-positive patient with known diagnosis of AS for 7 years, who developed a paravertebral abscess in the left erector spinae muscle due to brucellosis, is presented in this paper. This case report illustrates two important points; first, co-occurrence of AS and brucellosis in the same patient, and second, posterior element involvement with abscess formation in erector spinae muscle, which has not been previously reported. Magnetic resonance imaging is a sensitive method for detecting spinal brucellosis and extent of infection throughout paravertebral structures. Clinicians serving patients from areas with endemic brucellosis should not overlook the possibility of this infection in the presence of axial musculoskeletal symptoms, even among patients with AS. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: abscess; ankylosing spondylitis; brucellosis; paravertebral; sacroillitis